O-012 Peri-procedural complications, clinical outcomes and recurrence/retreatment rates after endovascular versus surgical treatment of intracranial aneurysms: a real-world assessment from the NVQI-QOD cerebral aneurysm registry. (23rd July 2022) - Bauknight, W; Noorani, S; Abdalla, R; Tejada, J; Church, E; Sahlein, D; Howington, J; Ansari, S
Abstract : Introduction: Improved outcomes after endovascular treatment of ruptured aneurysms were shown in ISAT (N=2143), with improved functional independence over surgical clipping. Many acknowledge these data have been extrapolated to non-ISAT and unruptured aneurysm populations, though some trials (e.g., BRAT) suggested less significant differences. Finally, most studies also suggest fewer peri-procedural complications with endovascular versus surgical treatment, though discrepancy exists in this literature. Despite increasing adoption of endovascular treatment, higher recurrence/retreatment rates have questioned the durability compared to surgery. We report peri-procedural complications, clinical outcomes, and retreatment rates from the NQVI-QOD Cerebral Aneurysm Registry (N=4250) to demonstrate the real-world practice of intracranial aneurysm treatment, providing important quality and performance benchmarks. Methods: We analyzed 4250 aneurysm cases from the 2015–2021 NQVI-QOD database for demographic/risk factors, presentations, aneurysm characteristics, treatment types, peri-procedural complications, angiographic and clinical outcomes at discharge and follow-up, and recurrence/retreatment rates across 4 subsets: Ruptured-Endovascular (N= 1522), Ruptured-Surgical (N=208), Unruptured-Endovascular (N=2224), and Unruptured-Surgical (N=296) to determine current treatment benchmarks for endovascular versus surgical management of ruptured and unruptured aneurysms. Descriptive analyses, followed by statistical differences in ordinal and categorical variables between endovascular and surgical treatment for unruptured and ruptured aneurysms were performed. Results: Intra-operative complications occurred in 6.2% endovascular vs 4.6% surgical patients (p=0.02), with thrombus formation and aneurysm rupture the most common endovascular and surgical complications, respectively. Post-operative complications occurred in 13.4% endovascular vs 23.1% surgical patients (p=<0.01), with infection and ischemic stroke the most common among ruptured and unruptured aneurysms respectively, both lower in endovascular patients (p<0.01). Although there was no difference in in-hospital mortality, 66% endovascular vs 55% surgical patients (p=0.01) were functionally independent at discharge after treatment of ruptured aneurysms (78% endovascular vs 72% surgical patients (p=0.02) discharged to home/rehab). For unruptured aneurysms, 94% endovascular vs 79% surgical patients (p=<0.01) were functionally independent at discharge (96% endovascular vs 92% surgical patients (p=0.3) discharged to home/rehab). At follow-up of ruptured aneurysms, 92% endovascular vs 72% surgical patients (p=<0.01) were functionally independent (94% endovascular vs 79% surgical (p=<0.01) living at home). At follow-up of unruptured aneurysms, 96% of endovascular vs 88% surgical patients (p=0.02) were functionally independent (97% endovascular vs 98% surgical (p>0.5) living at home). Post-procedure angiographic outcomes were similar for ruptured and unruptured aneurysms. Recurrence/retreatment occurred in 15% endovascular (21% ruptured, 11% unruptured) vs 8% surgical patients (p<0.01). Conclusion: Endovascular treatment of intracranial aneurysms was associated with better overall clinical outcomes than surgical clipping with improved disability free survival and better disposition at discharge or follow-up, across both ruptured and unruptured aneurysms. Although intraoperative complications were higher for ruptured aneurysms treated with endovascular treatment, there was no difference in unruptured aneurysms versus surgical clipping. Post-operative complications were lower for the endovascular cohort regardless of presentation. Overall, these data support ongoing primary adoption of endovascular treatment of both ruptured and unruptured aneurysms, though the long-term effects of reduced durability and increased recurrence/retreatment rates remains unclear. Disclosures: W. Bauknight: None. S. Noorani: None. R. Abdalla: None. J. Tejada: None. E. Church: None. D. Sahlein: None. J. Howington: None. S. Ansari: None.